1966
DOI: 10.3758/bf03328371
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ observing and heart period responses as related to novelty of visual stimuli

Abstract: No justification was found for computing an average reliability estimate although fairly high interobserver correlations were obtained for judgments of infants' fixation times.No intrastimulus decrement was found in observing times, whereas heart period responses when adjusted for prestimulus levels showed across-trial changes, but differentially for males and females. Relationships between observation duration and degree of interstimulus nove lty were contingent upon stimulus sequence and tended to be nonmono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

1967
1967
1978
1978

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Friedman et al (1974) demonstrated decremented visual fixation and subsequent recov-ery of fixation to a highly discrepant stimulus for both sexes, but found that only the female newborns showed response recovery to a moderately discrepant stimulus. Monitoring cardiac responses, Meyers and Cantor (1966) found that female infants' heart rate decelerations decreased with repeated stimulus presentations, evidencing reduced attention, while the males'decelerations increased in frequency over the course of the experiment. With regard to sex differences in the opposite direction, Cohen et al ( , 1971 and Pancratz and Cohen (1970) found that males', but not females', visual flXations habituated with repeated viewing of a stimulus.…”
Section: Incidence Of Sex Difference Findingsmentioning
confidence: 96%
See 1 more Smart Citation
“…Friedman et al (1974) demonstrated decremented visual fixation and subsequent recov-ery of fixation to a highly discrepant stimulus for both sexes, but found that only the female newborns showed response recovery to a moderately discrepant stimulus. Monitoring cardiac responses, Meyers and Cantor (1966) found that female infants' heart rate decelerations decreased with repeated stimulus presentations, evidencing reduced attention, while the males'decelerations increased in frequency over the course of the experiment. With regard to sex differences in the opposite direction, Cohen et al ( , 1971 and Pancratz and Cohen (1970) found that males', but not females', visual flXations habituated with repeated viewing of a stimulus.…”
Section: Incidence Of Sex Difference Findingsmentioning
confidence: 96%
“…Thirty-four of the 72 studies reviewed produced data pertinent to the issue of sex differences. Of these, seven (21%) found sex differences in habituation: Four investigations showed that rate of habituation and/or degree of discriminative response recovery were greater for male infants (Cohen, DeLoache, & Rissman, 1975;Cohen, Gelber, & Lazar, 1971;Cornell & Strauss, 1973;Pancratz & Cohen, 1970), while three demonstrated superior female perfonnance (Caron & Caron, 1969;Friedman, Bruno, & Vietze, 1974;Meyers & Cantor, 1966).…”
Section: Incidence Of Sex Difference Findingsmentioning
confidence: 99%
“…A second methodological strategy has involved short-term familiarization and testing of changes in attentional indexes within one brief session. Generally, these studies also suggest that duration of attention is greater to novel than to familiar stimuli (Fantz, 1964;Meyers & Cantor, 1966, 1967Saayman, Ames, & Moffet, 1964; but see Lewis, Bartels, Fadel, & Campbell, 1966). In each supporting case, however, the result was qualified by an interaction with familiarization rate, class of stimuli, sex, or specific stimulus preferences.…”
mentioning
confidence: 94%
“…Finally, some investigators have observed sex differences in habituation to simple visual stimuli (Horowitz & Paden 1969;Meyers & Cantor 1966;Pancratz & Cohen 1970), and some have found sex differences in the response to novel stimuli (e.g., Meyers & Cantor 1967;Pancratz & Cohen 1970).…”
mentioning
confidence: 97%